Entrepreneurship education and entrepreneurial intention of Chinese college students: Evidence from a moderated multi-mediation model - Gao, Yuan; Qin, Xiao (Frontiers in Psychology, 2022)
Purpose-Entrepreneurship has played an active role in promoting economic and population integration and social mobility. In order to promote economic and social development, the Chinese government and universities have launched entrepreneurship education courses and encouraged college students to participate in entrepreneurship competitions to enhance entrepreneurial knowledge, entrepreneurial ability and entrepreneurial intention. However, the entrepreneurial intention of Chinese college students is still not high. How should entrepreneurial education be carried out? Can entrepreneurial competitions and entrepreneurial self-efficacy be an effective medium for the impact of entrepreneurial education on entrepreneurial intention? Whether family income is a moderating factor affecting college students' entrepreneurial intention? This is the purpose of this research. Design/methodology/approach- Quantitative methods were used to collect 351 sample data, and a theoretical model of entrepreneurial intention was constructed. In the model, entrepreneurial competition and entrepreneurial self-efficacy were introduced as mediating variables, and family income was used as a moderating variable. Findings-The results show that entrepreneurial self-efficacy has a partial mediating effect between entrepreneurial education and entrepreneurial intention, but the effect is smaller than the chain mediating effect of entrepreneurial competition and entrepreneurial self-efficacy. Family income positively moderates the relationship between entrepreneurial education and entrepreneurial intention and the relationship between entrepreneurial self-efficacy and entrepreneurial intention. Originality/value-This study reveals the black box of the formation mechanism of college students' entrepreneurial intention. It affirms the role of the Chinese government in promoting entrepreneurship competitions, and at the same time provides empirical evidence for the effective development of entrepreneurial practice activities, and provides theoretical reference for entrepreneurial policy makers.